Enzymatic Synthesis of Thymol Octanoate, a Promising Hybrid Molecule - Sanchez, Daniel Alberto; Tonetto, Gabriela Marta; Ferreira, María Luján (Catalysts)
Interest in the synthesis and application of thymol esters has increased in recent years dueto the numerous applications associated with its biological activities. The enzymatic synthesis ofthymol octanoate by esterification of thymol and octanoic acid was explored using soluble lipasesand immobilized lipase biocatalysts in solvent-free systems. Candida antarctica lipase B in its solubleform was the most active biocatalyst for this reaction. Different thymol and lipase feeding strategieswere evaluated to maximize thymol octanoate production. The results suggest that there could belipase inhibition by the ester product of the reaction. In this way, the optimal reaction condition wasgiven using a thymol/acid molar ratio of 1:4 mol/mol. Under these conditions the conversion ofthymol was close to 94% and the lipase maintained more than 90% of its initial activity after thereaction, showing the potential of the enzyme to be used in successive reaction cycles. Fil: Sanchez, Daniel Alberto. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina. Universidad Nacional del Sur. Departamento de Ingeniería Química; Argentina Fil: Tonetto, Gabriela Marta. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina. Universidad Nacional del Sur. Departamento de Ingeniería Química; Argentina Fil: Ferreira, María Luján. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Bahía Blanca. Planta Piloto de Ingeniería Química. Universidad Nacional del Sur. Planta Piloto de Ingeniería Química; Argentina. Universidad Nacional del Sur. Departamento de Química; Argentina